Block copolymer self-assembly: exploitation of hydrogen bonding for nanoparticle morphology control via incorporation of triazine based comonomers by RAFT polymerization - Haque, Farah; Thompson, Steven W.; Ishizuka, Fumi; Kuchel, Rhiannon P.; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (Small, 2024)
Synthesis of polymeric nanoparticles of controlled non-spherical morphology is of profound interest for a wide variety of potential applications. Self-assembly of amphiphilic diblock copolymers is an attractive bottom-up approach to prepare such nanoparticles. In the present work, RAFT polymerization is employed to synthesize a variety of poly(N,N-dimethylacrylamide)-b-poly[butyl acrylate-stat-GCB] copolymers, where GCB represents vinyl monomer containing triazine based Janus guanine-cytosine nucleobase motifs featuring multiple hydrogen bonding arrays. Hydrogen bonding between the hydrophobic blocks exert significant influence on the morphology of the resulting nanoparticles self-assembled in water. The Janus feature of the GCB moieties makes it possible to use a single polymer type in self-assembly, unlike previous work exploiting, e.g., thymine-containing polymer and adenine-containing polymer. Moreover, the strength of the hydrogen bonding interactions enables use of a low molar fraction of GCB units, thereby rendering it possible to use the present approach for copolymers based on common vinyl monomers for the development of advanced nanomaterials.

Synthesis and film formation of aqueous emulsion polymer latexes featuring hydrogen bonding via a janus guanine-cytosine base monomer - Thompson, Steven W.; Li, Joanna; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (ACS APPLIED POLYMER MATERIALS, 2024)
Keywords: Emulsion polymerization; Film formation; Hydrogenbonding; Supramolecular networks

Morphology rearrangement by mixing of internally hydrogen-bonded nanoparticles comprising triazine-based amphiphilic diblock copolymers - Haque, Farah; Thompson, Steven W.; Ishizuka, Fumi; van der Tol, Joost J. B.; Singh, Dharmendra; Sanjayan, Gangadhar J.; Zetterlund, Per B. (Macromolecules, 2025)
The self-assembly of block copolymers holds significant potential for designing functional nanoparticles in materials science, nanomedicine, and nanotechnology. While the self-assembly of amphiphilic diblock copolymers is relatively well understood, the influence of specific supramolecular interactions, particularly hydrogen bonding, in directing their morphological behavior remains largely unexplored. In this study, it was demonstrated that nanoparticles self-assembled in water/DMSO (75/25 vol/vol; 2 mg/mL) comprising amphiphilic diblock copolymers with a small amount of triazine-based guanine-cytosine (GCB) motifs incorporated in the hydrophobic block can undergo spontaneous rearrangement into new morphologies on mixing. For example, mixing spheres with vesicles resulted in spontaneous transformation into worms (nanofibers), and this transformation was accelerated at elevated temperature. The hydrogen bonding motif features three complementary hydrogen bonding sites on either side of the nucleobase unit, thereby having a Janus character. Amphiphilic diblock copolymers comprising dimethyl acrylamide (hydrophilic segment) and n-butyl acrylate (hydrophobic segment) were synthesized by reversible addition-fragmentation chain transfer (RAFT) polymerization with a variable content of acrylate monomer functionalized with the Boc-protected form of the GCB motif as part of the hydrophobic segment. The present work represents a completely new approach for controlling self-assembly processes, paving the way for the design of functional nanoparticles for a range of applications.